Analisis Pasar Uang Pada Perekonomian Negara ASEAN - Nurhayati, Nurhayati; Pramana, Jajang Rangga (Lembaga Penerbitan Unversitas Esa Unggul, 2023)
The ASEAN economy cannot be separated from the economic crisis that occurred in the international market. The government and central bank in making monetary policy must take the right decisions to maintain stable currency values and suppress economic conditions if there is pressure from outside ASEAN countries. Money market analysis is used to see the influence of interest rates and income levels in the money market. This research uses data for the past 5 years from 2015-2020 and uses market analysis to discuss interest rates and income levels in each ASEAN country, using a two-stage least squares simultaneous equation model. The data taken are Gross Domestic Product, Domestic Interest Rates, Money Supply (M2), Inflation, Federal Reserve Interest Rates, Inflation Expectations. Based on the test results, it shows that the variables that have an influence on GDP are Interest Rates, Money Supply, and Inflation, while the Federal Reserve Interest Rate and Inflation Expectations have no influence on GDP